Molecular detection of type III secretory toxins in Pseudomonas aeruginosa isolates - Jarjees, Khanzad Khudhur (Cellular and Molecular Biology, 2020)
Pseudomonas aeruginosa has been known as a common unscrupulous pathogen that reasons cause nosocomial infections in patients with immunocompromise. Infection with multi-drug resistant Pseudomonas aeruginosa infection in many patients is a public health problem. The bacterium causes urinary tract infections, respiratory tract infections, skin inflammation and inflammation, soft tissue infections, bacteremia, bone and joint infections, gastrointestinal infections and various systemic infections, especially in patients with severe burns, cancer and AIDS, whose immune systems are suppressed. Among diverse virulence factors, the type III secretion system is known as a significant agent in virulence and development of antimicrobial resistance in P. aeruginosa. A total of 50 isolates of P. aeruginosa were gathered from burn wound and milk specimens. Documentation and antimicrobial susceptibility evidence were performed using the VITEK 2 system. Multiplex PCR was done to detect the secretion toxins-encoding genes. Out of 50 samples: 45/225 (20%) burn wound and 6/120 (5%) raw milk samples were found positive for P. aeruginosa. The multiplex PCR analysis of ExoT and ExoY genes showed that all P. aeruginosa 50 (100%) were positive. The occurrence of the ExoS and ExoU genes was 97.7% and 86.6% among clinical isolates while none of the raw milk isolates harbored the ExoU gene and 60% of them carried the ExoS gene. The results found 20 (40%) of isolates were multidrug resistance and the most effective antibiotics against clinical isolates were Ciprofloxacin and Meropenem. The aim of this study was to prevalence the exotoxin genes encoded type III secretion system and pattern of antimicrobial susceptibility of P. aeruginosa isolated from clinical and raw milk specimens.